Pathogenesis of Staphylococcus aureus necrotizing pneumonia: the role of PVL and an influenza coinfection. Issue 10 (October 2013) - Löffler, Bettina; Niemann, Silke; Ehrhardt, Christina; Horn, Dagmar; Lanckohr, Christian; Lina, Gerard; Ludwig, Stephan; Peters, Georg
Only recently necrotizing pneumonia was defined as a specific disease entity that is caused by a Panton-Valentine leukocidin (PVL)-producing Staphylococcus aureus strain and is frequently preceded by an influenza infection. Necrotizing pneumonia is characterized by a sudden onset and rapid worsening of symptoms, leukopenia, airway hemorrhages, severe respiratory failure and a high mortality rate. Despite clear epidemiological data, the function of PVL in necrotizing pneumonia has been controversially discussed due to conflicting results from different disease models. Furthermore, there are many proposed mechanisms how a viral infection could facilitate and interact with a bacterial superinfection. In this review, we summarize current data from 43 clinical cases and results from various infection models on necrotizing pneumonia. We discuss the contribution of S. aureus PVL and a preceding influenza infection and present a concept of the pathogenesis of necrotizing pneumonia.